Cyclic flow shop scheduling problem with two-machine cells - Bożejko, Wojciech; Gnatowski, Andrzej; Idzikowski, Radosław; Wodecki, Mieczysław (Archives of Control Sciences, 2017)
Abstract In the paper a variant of cyclic production with setups and two-machine cell is considered. One of the stages of the problem solving consists of assigning each operation to the machine on which it will be carried out. The total number of such assignments is exponential. We propose a polynomial time algorithm finding the optimal operations to machines assignment.